Age and sex differences in the relationship of body weight changes with colon cancer risks: A nationwide cohort study - Jae Hyun Kim; Young Ko; Hyun Jung Kim; Seun Ja Park (Scientific Reports)
Abstract Colon cancer is a significant health concern, and obesity is a well-established risk factor. However, previous studies have mainly focused on assessing body weight as a risk factor for colon cancer at a specific time point. This nationwide cohort study investigated the association between body weight changes, which can fluctuate throughout an individual’s lifespan, and the incidence of colon cancer using the South Korean population database provided by the National Health Insurance Service (NHIS). Participants who underwent biennial health screenings between 2004 and 2006, and had follow-up health check-ups between 2014 and 2016, were included in this study. Body weight changes were categorized as follows: < 5%, decrease 5–20%, decrease > 20%, increase 5–20%, or > 20%. The primary outcome was the incidence of newly diagnosed colon cancer. Statistical analysis was used to examine the relationship between body weight changes and the incidence of colon cancer stratified according to age and sex. The Kaplan–Meier method estimated the cumulative incidence of colon cancer, and Cox proportional hazards models were used to calculate hazard ratios (HR) and 95% confidence intervals (CI), adjusting for confounding factors. The analysis included data from 10,332,397 individuals, with a mean (± SD) age of 45.5 ± 13.1 years, and 54.9% were male. In males with a body mass index (BMI) range of 18–30 kg/m2, both a weight gain of 5–20% (HR 1.07, P > z 0.01 [95% CI 1.02–1.13]) and weight gain > 20% (HR 1.27, P > z 0.03 [95% CI 1.03–1.56]) were associated with an increased risk for colon cancer. In addition, males < 40 years of age exhibited a higher risk for colon cancer with > 20% weight gain (HR 1.65, P > z < 0.001 [95% CI 1.18–2.30]). Whereas, females within the BMI range of 18–30 kg/m2 who exhibited > 20% weight loss demonstrated a reduced risk (HR 0.77, P > z 0.04 [95% CI 0.60–0.98]). Moreover, females ≥ 40 years of age, who experienced weight loss > 20%, exhibited a decreased risk for colon cancer (HR 0.76; P > 0.02 [95% CI 0.60–0.96]). This nationwide cohort study demonstrated a relationship between body weight changes and the incidence of colon cancer, with differences based on sex and age. In particular, avoiding weight gain is crucial for males < 40 years of age, whereas weight loss could be beneficial for females > 40 years of age in reducing the risk of colon cancer.